Maternal body mass index, parity and smoking are associated with human milk macronutrient content after preterm delivery - Burianova, Iva; Bronsky, Jiri; Pavlikova, Marketa; Janota, Jan; Maly, Jan (Early human development, 2019)
Maternal characteristics may be associated with human milk macronutrients but no definite conclusions have been made to date. This study aimed to determine the relationship of maternal-associated factors on the content of macronutrients in human milk for the first six weeks after preterm delivery. Prospective observational cohort study. Milk samples were collected from mothers after premature birth between 24 + 0–35 + 6 weeks. Macronutrients and energy content were analyzed by mid-infrared transmission spectroscopy. Demographic and anthropometric data from mothers were systematically recorded. A total 1.558 human milk samples from 192 mothers were analyzed. Colostrum: higher protein (p = 0.001) and lower carbohydrate content (p = 0.003) were present in primiparous compared to multiparous milk. Vaginal birth was associated with increased carbohydrate content (p = 0.021). Fat and energy content in colostrum was not related to any maternal characteristics. Mature human milk: similarly to colostrum, higher protein content (p = 0.001) and lower carbohydrates content (p = 0.022) were observed in primiparous compared to multiparous milk. The mode of delivery was found to be another factor possibly influencing protein and carbohydrate levels (p = 0.036, p = 0.003, respectively). Pre-pregnancy obesity was associated with increased fat (p = 0.030) and energy content (p = 0.020) in human milk. On the contrary, smoking had a negative relationship to fat and energy content (p = 0.026, p = 0.007, respectively). Human milk macronutrient concentration after preterm delivery is associated with pre-pregnancy obesity, parity, mode of delivery and smoking. The impact of maternal factors on human milk composition should be taken into account in a strategy of feeding in premature infants. •Limited data are available on the influence of maternal characteristics on the human milk.•Maternal characteristics are associated with macronutrients and energy of human milk after premature birth.•Primiparous mothers have higher protein and lower carbohydrates content in human milk. than multiparous.•Obese mothers are found to have higher fat and energy content in human milk.•Smoking is negatively associated with milk fat content.